Genome-wide identification and expression pattern analysis of NAC family in Taxus yunnanensis and the TyuNAC30 role in paclitaxel production - Jiangtao Fan; Yong Wang; Mengke Dou; Qiuhong Hu; Qing Li; Shengmei Gan; Mingwei Jing; Gang Wang; Xiong Huang (BMC Genomics)
Abstract Background The NAC transcription factor family represents a large group of plant-specific genes involved in various biological processes, including secondary metabolite biosynthesis, responses to biotic and abiotic stresses, and hormone signaling. Taxus yunnanensis, a well-known medicinal plant, is the natural source of the anticancer diterpene paclitaxel. Despite the biological importance of NAC transcription factors, no comprehensive genome-wide study of the NAC gene family has been conducted in T. yunnanensis. Results In this study, 44 NAC genes were identified from the T. yunnanensis genome. Gene structure analysis revealed that the number of exons ranged from 1 to 7, with most genes containing 2 to 3 exons. Chromosomal mapping showed an uneven distribution of TyuNACs across the 11 chromosomes. Duplication type analysis indicated that dispersed duplication is the primary mechanism driving the expansion of the TyuNACs, accounting for the largest proportion (24 genes), followed by tandem (12 genes) and proximal duplications (8 genes); no whole-genome or segmental duplication events were detected. Cis-regulatory element analysis suggested that TyuNACs are involved in key biological processes such as development, light response, stress adaptation, and hormone signaling. Expression profiling revealed diverse tissue-specific expression patterns, with most TyuNACs highly expressed in bark. Moreover, qRT-PCR analysis demonstrated that several TyuNACs respond to methyl jasmonate (MeJA) treatment. Yeast one-hybrid and related assays revealed that TyuNAC30 functions as a negative regulator of TyuDBTNBT, a key enzyme gene in the paclitaxel biosynthetic pathway. Conclusion This study presents the comprehensive genome-wide characterization of the NAC transcription factor family in T. yunnanensis. The findings underscore the predominant role of dispersed duplication in the expansion of the TyuNAC family, with additional contributions from tandem and proximal duplications. Importantly, TyuNAC30 was identified as a negative regulator of TyuDBTNBT, suggesting a key role in the transcriptional regulation of paclitaxel biosynthesis. These findings offer valuable insights for further exploration of the functional roles of NAC genes, particularly their involvement in the regulatory mechanisms underlying paclitaxel biosynthesis.